Releasing Knowledge for Practice in Human and Social Service Organizations - Moxley, David P. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book will advance readers' understanding of the knowledge development, building and/or management process within human service organizations, informed by the author's experience in human service organizations, as consultant, and practitioner. Readers can come to understand the knowledge building process, and gain a conceptual framework in building organizational knowledge for the advancement of human services practice. The importance of knowledge management in social welfare and human service is twofold. Knowledge management is about an organization managing what it knows in order to achieve more competent and more effective performance. It also is about how domains and fields of practice may transform themselves over time through the purposeful creation and destruction of knowledge. Knowledge management can be a cornerstone of today's human service and social welfare organizations and may be a principal strategy for effecting innovation and evolution in the ways societies address and meet human needs. David P. Moxley is Professor and Assistant Dean for Behavioral Health in the University of Alaska Anchorage College of Health, USA, where he also serves as Director of the School of Social Work and Department of Human Services.
Chapter 1 Knowledge Management in the Human Service Domain -- Chapter 2 The Relevance of Organizational Knowledge Management -- Chapter 3 Societal, Social, Technical, and Organizational Aspects of Knowledge Management -- Chapter 4 Structuring the Knowledge Management System -- Chapter 5 Dimensions and Competencies of the Knowledge Management System -- Chapter 6 Capacities for Knowledge Management in the Human Services -- Chapter 7 Conclusion: Releasing Knowledge for Practice Advancement through Transformative Action.
Keywords: Community development; Social service; Industrial sociology; Sociology; Social Work and Community Development; Sociology of Work; Sociology; Social Care